Using Supply Chain Management Strategy for Regional Economic Clusterization in Kazakhstan’s Chemical Industry - Issakova, S. A.; Kudabayeva, L. A.; Nauryzbekova, A. Ye.; Mussaeva, G. K.; Tuleyeva, G. T.; Zhantayeva, A. M.; Suleimenova, I. K. (ExcelingTech, 2019)
This article develops an approach to forming innovative development clusters in Kazakhstan’s chemical industry as an opportunity to promote the effectiveness of the sector’s development and to increase its competitive advantage based on the supply chain management. An expert evaluation method is used to form a system of indicators for assessing innovative development in the country’s regional chemical industry. A scaling technique was also incorporated to distinguish these clusters according to the quality levels of innovative development among the chemical industry regions in a modern context, with industrial gas production as an example. Two chemical clusters of innovative development in Kazakhstan’s regions were formed though a cluster analysis – and their economic efficiency substantiated – using multivariate linear regression modeling. The efficiency from creating Chemical Cluster No. 0 for innovative development indicates that its total regional product would grow by 0.68%, while Cluster 5 exhibited an efficiency of 4.23%. The presented methodological approach is based on a horizontal integration of the manufacturers and suppliers of chemical products, and considers specific characteristics of the industry’s operation; this allows for the creation of chemical clusters with highly efficient communication in the innovation process. The research findings contribute to modernizing the country’s chemical industry and increasing its competitive capacity in the international market.